A method for quantitatively evaluating the quality of gelatinization of modified starch

CN117589642BActive Publication Date: 2026-10-20FOSHAN HAITIAN (JIANGSU) SEASONING FOOD CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311449305.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-02
Publication Date
2026-10-20
Estimated Expiration
2043-11-02

AI Technical Summary

Technical Problem

该研究虽然能迅速测得淀粉及其制品的α-化程度,准确率高,用时短,成本低;但该方法仅能针对淀粉糊化前期的α-化程度的准确测定,对于淀粉糊化后期、淀粉颗粒破碎导致粘度下降后,其检测结果则不准确

Benefits of technology

[0043]本申请提供了一种量化评估变性淀粉糊化质量的方法,本申请通过研究变性淀粉糊化过程中的体积加权平均粒径大小,粒径分布累积<35μm的占比分布变化情况,量化评估变性淀粉的糊化质量,可以控制变性淀粉的糊化程度和破碎程度,提升淀粉的糊化一致性,以提高变性淀粉的增稠稳定性能,使产品仍具有良好的质量稳定性;本申请通过测试变性淀粉的粒径变化来优化糊化工艺,提升变性淀粉的颗粒完整性,减少粘度损失,达到降低变性淀粉用量或提升变性淀粉粘度的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117589642B_ABST
    Figure CN117589642B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of food detection, and particularly discloses a method for quantitatively evaluating the gelatinization quality of modified starch. The application quantitatively evaluates the gelatinization quality of the modified starch by studying the volume-weighted average particle size in the gelatinization process of the modified starch, the change of the proportion distribution of the cumulative <35 mu m particle size distribution, can control the gelatinization degree and the crushing degree of the modified starch, improve the gelatinization consistency of the modified starch, improve the thickening stability of the modified starch, and make the product still have good quality stability; the application optimizes the gelatinization process by testing the particle size change of the modified starch, improves the particle integrity of the modified starch, reduces the viscosity loss, and achieves the purposes of reducing the amount of the modified starch or improving the viscosity of the modified starch.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of food testing technology, and in particular to a method for quantitatively evaluating the gelatinization quality of modified starch. Background Technology

[0002] The properties of starch and starch products are affected by factors such as material composition, degree of modification, amylose / branched starch content, and degree of polymerization. For products using modified starch as a thickener, the degree of gelatinization of the modified starch has a significant impact on the viscosity stability of the product during processing. In many foods containing modified starch, the starch may contain both intact and broken starch at the same processing stage, leading to different viscosity trends. When the starch granules are intact, gelatinization begins, and the viscosity of the paste increases. When the starch content is sufficient or broken starch is present, continued gelatinization causes the granules to degrade and break down, resulting in a decrease in paste viscosity. However, conventional methods such as microscopic examination, centrifugation, viscosity measurement, or absorbance measurement cannot accurately reflect the changes of modified starch in the product. This is because these methods can only qualitatively determine the trend of modified starch gelatinization and cannot simultaneously and accurately determine the degree of gelatinization and breakage of the starch granules.

[0003] For example, patent CN107631991A discloses a method for rapid detection of starch gelatinization in trace amounts. First, a standard curve for starch gelatinization is constructed based on the absorbance values ​​at the corresponding points. Second, the absorbance values ​​of the starch solution to be tested are measured at these points. Finally, the measured absorbance values ​​are substituted into the standard curve formula to calculate the gelatinization degree of the starch solution. This method is only suitable for quantitatively evaluating the thermal gelatinization of starch particles, because the absorbance changes significantly after starch is broken, making it unsuitable for accurately testing the degree of gelatinization after starch breakage.

[0004] For example, patent CN111721900A discloses a method for detecting the degree of α-oxidation of starch and its products, including: (1) preparing at least two starch products with known degrees of α-oxidation into dispersions of the same concentration, wherein the mass fraction of the dispersion is 0.4% to 4%; (2) taking samples of the same mass of dispersion, separating them under the same conditions, and measuring the sediment volume; (3) the degree of α-oxidation and the sediment volume satisfy the following linear equation: A = aV + b, where A is the degree of α-oxidation, V is the sediment volume, and a and b are parameters; combining the measured sediment volumes and corresponding degrees of α-oxidation with the above linear equation, calculating the parameters a and b, and obtaining the linear equation; (4) taking the starch product to be tested, processing it according to the conditions of steps (1) and (2), measuring the sediment volume Vx, and substituting Vx into the above linear equation to obtain the degree of α-oxidation of the starch product to be tested. While this study can rapidly measure the degree of α-gelatinization of starch and its products with high accuracy, short processing time, and low cost, the method is only accurate in determining the degree of α-gelatinization in the early stage of starch gelatinization. The results are inaccurate in the later stages of starch gelatinization, after starch granules break down and viscosity decreases. This is because: when starch is not broken down, the starch sediment volume gradually increases, which is positively correlated with the degree of gelatinization; when starch begins to break down, the starch viscosity is higher and the sediment volume is larger. However, as starch further gelatinizes and continues to break down, the viscosity of the starch paste decreases. At this point, using sediment volume to determine the degree of gelatinization becomes inaccurate, leading to inaccurate test results.

[0005] For example, testing the viscosity of starch paste can ensure that the starch reaches a very high viscosity, but the process may involve unstable starch particles and insufficient gelatinization viscosity stability. Therefore, the viscosity method mainly assesses the gelatinization properties of raw starch and cannot quantify the gelatinization quality of starch. On the other hand, microscopic examination can better determine the integrity of starch particles, but it cannot quantify the degree of starch gelatinization.

[0006] In summary, all of the above methods suffer from the problem of difficulty in quantitatively determining the endpoint of gelatinization quality, and therefore, there is still room for improvement. Summary of the Invention

[0007] The purpose of this application is to overcome the shortcomings of the prior art and provide a method for quantitatively evaluating the gelatinization quality of modified starch. This method overcomes the deficiencies of individual viscosity methods and microscopic methods, ensuring sufficient starch gelatinization without causing problems such as water separation and viscosity decrease during shelf life due to over-gelatinization. By studying the changes in viscosity, particle size, and starch granules during the gelatinization process of modified starch, this application enables modified starch to maintain intact starch granules under conditions of sufficient gelatinization, thereby increasing viscosity or reducing the amount of modified starch required.

[0008] To achieve the above objectives, the technical solution adopted in this application is as follows:

[0009] In a first aspect, this application provides a method for quantitatively evaluating the gelatinization quality of modified starch, comprising the following steps:

[0010] S1. Prepare modified starch into starch slurry, heat and gelatinize to obtain the starch paste to be tested;

[0011] S2. Dilute the starch paste obtained in step S1, and detect the first volume-weighted average particle size and the first particle size distribution accumulation of the diluted starch paste.

[0012] S3. Compare the first volume-weighted average particle size and the first particle size distribution accumulation with the preset target parameter range, and evaluate the gelatinization quality of the starch paste to be tested based on the comparison results.

[0013] Most existing methods for assessing gelatinization quality are only applicable to the assessment of gelatinization quality before complete gelatinization of starch, and cannot be applied to the assessment after complete gelatinization when starch breakage occurs. However, this application can assess the gelatinization quality of starch at different gelatinization stages. In particular, it can accurately assess the gelatinization quality of starch under conditions of complete gelatinization, so as to quantify the degree of gelatinization of the starch being assessed.

[0014] Modified starch is a water-insoluble granular substance. After gelatinization, modified starch tends to settle at lower viscosity and remains suspended at higher viscosity. Particle size analysis instruments can be used to test the size and distribution of starch particles. During the test, the number and size of particles are the main factors affecting the starch particle size measurement.

[0015] Because starch gelatinization involves water separation and swelling, the degree of swelling of modified starch and the integrity of starch granules can alter the volume and particle size of the starch granules. Through extensive research and experimentation, the inventors of this application have discovered that by testing the first volume-weighted average particle size and the cumulative first particle size distribution of the starch paste to be tested, and comparing them with a preset target parameter range, the gelatinization quality of the starch paste can be evaluated based on the comparison results. This application controls the first volume-weighted average particle size and the cumulative first particle size distribution of the starch paste to be tested within the preset target parameter range, which can improve the gelatinization viscosity of starch while ensuring the integrity of starch granules, thus achieving effective utilization of starch. The method of this application is simple to test, uses data analysis, and provides a more accurate judgment of the degree of starch gelatinization and starch breakage. Furthermore, the test data is stable and has good reproducibility.

[0016] In a preferred embodiment of the method for quantitatively evaluating the gelatinization quality of modified starch described in this application, in step S1, the heating temperature is 99-101°C, and the mass concentration of modified starch in the starch paste to be tested is 5.7%-6%.

[0017] This application uses thickening and stabilizing modified starch. The quality of modified starch gelatinization refers to achieving the highest viscosity of the modified starch under conditions such as heat and shear force. However, at the highest viscosity, modified starch is prone to insufficient stability, such as easy disintegration of starch granules and a decrease in viscosity. Therefore, the gelatinization quality of modified starch is not about obtaining the highest viscosity, but rather about achieving a certain degree of gelatinization so that starch pastes and starches of different gelatinization degrees have high viscosity and good quality stability in product applications, maximizing starch utilization while maintaining good quality stability.

[0018] Experiments have verified that the degree of starch gelatinization is not affected by the starch concentration when using modified starch of different mass concentrations. Therefore, this application has wide applicability and can be used to evaluate the degree of gelatinization of modified starch of different concentrations.

[0019] As a preferred embodiment of the method for quantitatively evaluating the gelatinization quality of modified starch described in this application, in step S2, pure water is used as the dispersion medium to dilute the starch paste obtained in step S1 to 1% to 2%, and the first volume-weighted average particle size and the first particle size distribution accumulation of the diluted starch paste are detected by a laser particle size analyzer, wherein the shading degree of the laser particle size analyzer is set to 15% to 20%.

[0020] In a preferred embodiment of the method for quantitatively evaluating the gelatinization quality of modified starch described in this application, the preset target parameter range is: a volume-weighted average particle size of 45–46 μm, and a cumulative particle size distribution <35 μm percentage distribution of 33–34%. Preferably, the volume-weighted average particle size is 45.53 μm, and the cumulative particle size distribution <35 μm percentage distribution is 33.5%.

[0021] This application studies the changes in the first volume-weighted average particle size and the cumulative proportion of the first particle size distribution during the gelatinization process of modified starch, and compares them with the preset target parameter range. This allows for the prediction of the influence of modified starch on the process. Because laser particle size analyzers are used to test large, water-insoluble particles like modified starch, even small volume changes can reflect the degree of gelatinization, making the test highly sensitive. The volume-weighted average particle size D[4,3] (hereinafter referred to as D[4,3]) reflects the degree of expansion of the modified starch. The cumulative proportion of particle size distribution / % D[<35μm] (i.e., the cumulative proportion of particle size <35μm, hereinafter referred to as D[<35μm] / %), where 35μm is determined by combining the volume-weighted average particle size of the modified starch at 0h of heat preservation, i.e., the initial volume-weighted average particle size, and particles smaller than this initial volume-weighted average particle size) reflects the integrity of the modified starch. The gelatinization of modified starch is a process of water separation and expansion. When the modified starch... As starch granules gradually increase, their density (D4,3) gradually increases, while the density (D<35μm) of small molecules gradually decreases. As modified starch continues to gelatinize, the number of modified starch granules further increases, and their D4,3 may increase or decrease. The proportion of small molecules with D<35μm / % gradually increases. However, with regelatinization, the modified starch begins to degrade, at which point the D4,3 of the modified starch decreases, and the proportion of small particles with D<35μm / % increases. By observing the changes in D4,3 and D<35μm / % during the gelatinization process, the particle stability of modified starch can be accurately assessed. Ultimately, the degree of gelatinization of modified starch can be controlled by observing the changes in D4,3 and D<35μm / %. Accelerated shelf-life quality verification can determine the impact of the degree of gelatinization on product quality, ultimately achieving control over the degree of gelatinization and ensuring the product maintains good quality stability.

[0022] This application controls the volume-weighted average particle size to be 45.53 μm and the cumulative proportion of particle size distribution <35 μm to be 33.5%, which results in starch paste samples having high viscosity, sufficient gelatinization, good viscosity stability, and stable quality during shelf life.

[0023] In a preferred embodiment of the method for quantitatively evaluating the gelatinization quality of modified starch described in this application, step S3 includes:

[0024] If the first volume-weighted average particle size is 45-46 μm, and the cumulative proportion of the first particle size distribution <35 μm is 33-34%, the gelatinization quality is best evaluated within this range.

[0025] If the first volume-weighted average particle size is >46μm, and the cumulative proportion of the first particle size distribution <35μm is >33%, then the gelatinization is excessive.

[0026] If the first volume-weighted average particle size is <45μm, and the cumulative proportion of the first particle size distribution <35μm is >33%, then gelatinization is incomplete or excessive. Further, the determination of whether it is incomplete or excessive gelatinization is based on the previous detection data (i.e., detection data less than the current gelatinization time) or the next detection data (i.e., detection data greater than the current gelatinization time – after continued gelatinization). If the volume-weighted average particle size in the previous detection data is smaller than the current first volume-weighted average particle size, or the cumulative proportion of the particle size distribution <35μm in the previous detection data is larger than the cumulative proportion of the first particle size distribution <35μm in the current detection data, then it is incomplete gelatinization. If the volume-weighted average particle size in the previous detection data is larger than the current first volume-weighted average particle size, or the cumulative proportion of the particle size distribution <35μm in the previous detection data is smaller than the cumulative proportion of the first particle size distribution <35μm in the current detection data, then it is excessive gelatinization. If the volume-weighted average particle size in the next detection data is larger than the current first volume-weighted average particle size, or if the proportion of particle size distributions with a cumulative value <35μm in the next detection data is smaller than the proportion of particle size distributions with a cumulative value <35μm in the current first detection data, then the gelatinization is incomplete. If the volume-weighted average particle size in the next detection data is smaller than the current first volume-weighted average particle size, or if the proportion of particle size distributions with a cumulative value <35μm in the next detection data is larger than the proportion of particle size distributions with a cumulative value <35μm in the current first detection data, then the gelatinization is excessive.

[0027] This application can accurately assess the particle stability of starch by varying the changes in D[4,3] and D[<35μm] / % during the gelatinization process of modified starch. Ultimately, the degree of starch gelatinization can be controlled by the changes in D[4,3] and D[<35μm] / %. By accelerating shelf-life quality verification, the impact of the degree of starch gelatinization on product quality can be determined, ultimately achieving the goal of controlling the degree of starch gelatinization so that the product still has good quality stability.

[0028] In a preferred embodiment of the method for quantitatively evaluating the gelatinization quality of modified starch described in this application, the preset target parameter range is obtained through the following steps:

[0029] S4. Prepare the modified starch into a starch slurry, heat and keep warm to obtain a starch paste sample;

[0030] S5. Dilute the starch paste sample obtained in step S4, and detect the second volume-weighted average particle size and the second particle size distribution accumulation of the diluted starch paste sample.

[0031] S6. The diluted starch paste sample obtained in step S5 is subjected to accelerated shelf life testing to detect the viscosity stability and water separation of the starch paste sample.

[0032] S7. Determine the preset target parameter range based on the second volume weighted average particle size and the second particle size distribution accumulation of the diluted starch paste sample, the viscosity stability of the starch paste sample, and the water separation situation.

[0033] In a preferred embodiment of the method for quantitatively evaluating the gelatinization quality of modified starch described in this application, in step S4, the heating temperature is 99–101°C, and the holding time is 0–9 h, preferably 1–6 h.

[0034] Different holding times have a significant impact on the viscosity and cumulative proportion of particles <35μm (D<35μm] / %) of starch paste samples. After holding for 5 hours, the viscosity of the modified starch paste gradually increases, the particles expand, and the proportion of small molecules (D<35μm] / %) gradually decreases, indicating that the starch absorbs water and expands during this stage, the particles become larger, and the proportion of small molecules gradually decreases. By the 6th hour of holding, the starch paste reaches its highest viscosity, and the proportion of small molecules (D<35μm] / %) begins to increase, indicating that the starch particles are fully gelatinized during this process, and the starch begins to swell and break down. With continued holding, the starch viscosity gradually decreases, and the proportion of small molecules (D<35μm] / %) gradually increases, indicating that the starch particles are too fully gelatinized during this process, and the starch continues to swell and break down.

[0035] Secondly, this application provides the application of the above-mentioned method for quantitatively evaluating the gelatinization quality of modified starch in improving starch utilization.

[0036] By controlling the volume-weighted average particle size D[4,3] of the modified starch gelatinization to be 45-46 μm and the cumulative particle size distribution D[<35 μm] / % to be 33%-34%, the gelatinization quality of the modified starch can be quantified. This ensures that the starch, under sufficient gelatinization, has intact particles and high viscosity and viscosity stability. If it is necessary to quantify the gelatinization quality of other modified starches, this method can be used for research and improvement, which can also achieve the purpose of improving starch gelatinization quality and increasing starch utilization efficiency.

[0037] Thirdly, this application provides the application of the above-mentioned method for quantitatively evaluating the gelatinization quality of modified starch in the preparation of oyster sauce products.

[0038] As a preferred embodiment of the application, the oyster sauce product comprises the following components in parts by weight:

[0039] The ingredients are 15 parts oyster sauce, 9 parts white sugar, 5 parts monosodium glutamate, 6 parts edible salt, 5 parts hydroxypropyl distarch phosphate, and 60 parts water. The volume-weighted average particle size of the oyster sauce product is controlled to be 45-46 μm, and the cumulative proportion of particles with a particle size distribution <35 μm is 33-34%.

[0040] Accelerated shelf-life testing was conducted by controlling different degrees of starch gelatinization in oyster sauce to verify the quality stability of starch with different degrees of gelatinization in the product and to establish a correlation with the shelf-life quality of starch. Currently, the volume-weighted average particle size of oyster sauce products is 41-43 μm, and the cumulative proportion of particle size distribution <35 μm in the starch paste samples is 35-37%. This confirms that the volume-weighted average particle size of starch in oyster sauce is 45-46 μm, and the cumulative proportion of particle size distribution <35 μm in the starch paste samples is 33-34%, which still indicates good shelf-life quality.

[0041] This application also determines the quality of starch with different degrees of gelatinization by assessing the shelf-life quality stability of starch pastes and starches with different degrees of gelatinization in products, and the correspondence between the average volume particle size and particle size distribution of starch. At the same time, it needs to take into account the starch viscosity and viscosity stability, so as to achieve the goal of fully utilizing the starch.

[0042] Compared with the prior art, this application has the following beneficial effects:

[0043] This application provides a method for quantitatively evaluating the gelatinization quality of modified starch. By studying the volume-weighted average particle size and the cumulative distribution of particles <35μm during the gelatinization process, this application quantitatively evaluates the gelatinization quality of modified starch. This method can control the degree of gelatinization and breakage of modified starch, improve the gelatinization consistency, and enhance the thickening stability of modified starch, ensuring that the product still has good quality stability. This application also optimizes the gelatinization process by testing the particle size change of modified starch, improving the particle integrity of modified starch, reducing viscosity loss, and achieving the goal of reducing the amount of modified starch used or increasing the viscosity of modified starch. Attached Figure Description

[0044] Figure 1 This is a graph showing the changes in viscosity and volume-weighted average particle size under different heat preservation times in Example 1;

[0045] Figure 2 This is a graph showing the effect of different heat preservation times on the viscosity and the proportion of particles with a cumulative particle size distribution <35μm in Example 1;

[0046] Figure 3 The graph shows the changes in viscosity and precipitation volume for different heat preservation times in Comparative Example 1.

[0047] Figure 4 The images show the microscopic examination results of starch paste samples with different heat preservation times in Comparative Example 1.

[0048] Figure 5 The images show the microscopic examination results of starch paste samples with different amounts of starch used in Example 2. Detailed Implementation

[0049] To better illustrate the purpose, technical solution, and advantages of this application, the following description will be provided in conjunction with the accompanying drawings and specific embodiments.

[0050] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0051] Example 1: Effects of different holding times on the volume-weighted average particle size and cumulative particle size distribution of starch paste samples Influence of the proportion of <35μm

[0052] S1. Modified starch is prepared into starch slurry, heated to 100°C, and kept at different temperatures for 0h / 1h / 2h / 3h / 4h / 5h / 6h / 7h / 8h / 9h to obtain starch paste samples. The mass concentration of modified starch in the starch paste samples is 6%.

[0053] S2. Using pure water as the dispersion medium, the starch paste samples obtained in step S1 with different heat preservation times were diluted to 1.5%. The volume-weighted average particle size D[4,3] (μm) and the proportion of cumulative particle size distribution <35μm were measured by a laser particle size analyzer. The shading degree of the laser particle size analyzer was set to 15%~20%. The test results are shown in Table 1 below.

[0054] Table 1. Results of changes in viscosity, volume-weighted average particle size, and cumulative proportion of particles <35 μm in starch paste samples under different heat preservation times.

[0055]

[0056] Meanwhile, viscosity tests and microscopic examinations were performed on the starch paste samples. The test results are shown in Table 1 and 2, respectively. Figure 4 As shown in Table 1, after heating and holding for 6 hours, the viscosity of the modified starch paste continued to increase, and its volume-weighted average particle size increased, indicating that the process was mainly characterized by the thickening and stabilization of intact starch. After holding for 6 hours, the viscosity of the starch paste gradually decreased, and the volume-weighted average particle size also gradually decreased, indicating that the modified starch gradually disintegrated and broke down during the holding process.

[0057] Refer to Table 1. Figure 1-2 After heating and holding the modified starch at a specific temperature, the viscosity of the starch paste gradually increased during the 5-hour holding period, and the particles expanded. The percentage of small molecule particles (D<35μm) gradually decreased, indicating that the starch absorbed water and swelled during this stage, resulting in larger particles and a gradually decreasing proportion of small molecule particles. By the 6th hour of holding, the starch paste reached its highest viscosity, and the percentage of small molecule particles (D<35μm) began to increase, by approximately 1.9%. This indicates that the modified starch particles were fully gelatinized during this process, and the modified starch began to swell and break down (from...). Figure 4 It can also be seen that as the temperature is maintained, the viscosity of the modified starch gradually decreases and the D[<35μm] / % small molecule particles gradually increase, indicating that the modified starch particles are gelatinized too thoroughly in this process, and the modified starch continues to swell and break down.

[0058] It should be noted that in the early stages of this application, viscosity and microscopic examination were used to help determine the gelatinization quality of modified starch, so related tests were carried out simultaneously. However, the ultimate goal is not to use methods such as viscosity and microscopic examination, which are broad or can only qualitatively determine the gelatinization quality of modified starch, but to control the gelatinization quality of modified starch with high precision, fast testing speed, and better quantification of volume-weighted average particle size and particle size distribution.

[0059] Comparative Example 1: Effect of different heat preservation times on the viscosity and sedimentation volume changes of starch paste samples

[0060] S1. Modified starch is prepared into starch slurry, heated to 100°C, and kept at different temperatures for 0h / 1h / 2h / 3h / 4h / 5h / 6h / 7h / 8h / 9h to obtain starch paste samples. The mass concentration of modified starch in the starch paste samples is 6%.

[0061] S2. Dilute the starch paste samples with different incubation times obtained in step S1 to 1.5%. Using a 15mL centrifuge tube, weigh 10mL of the dispersion, centrifuge at 5000RPM for 10min, and test the volume of the starch paste (precipitate volume) after centrifugation. Refer to Table 2.

[0062] Table 2. Results of changes in viscosity and sediment volume of starch paste samples at different heat preservation times.

[0063]

[0064] Refer to Table 2. Figure 3-4 Within 0-8 hours of incubation, the sediment volume of the starch paste gradually increased. From 9 hours onwards, the sediment volume began to decrease. However, the modified starch granules began to break down at 6 hours. With continued incubation, the more modified starch granules broke down, the greater the water-holding capacity of the starch paste became. The starch paste and water combined more easily, so even with the breakage of modified starch, the sediment volume of the starch paste still tended to increase. This indicates that controlling viscosity and sediment volume cannot accurately identify the gelatinization quality of modified starch. Microscopic images can provide a relatively direct qualitative assessment of the integrity and breakage state of the modified starch paste, but cannot quantify the degree of gelatinization.

[0065] Example 2: Effects of different concentrations of modified starch on the viscosity, volume-weighted average particle size, and other properties of starch paste samples. The effects of particle size distribution accumulation and sediment volume change

[0066] Modified starches with different amounts of starch were heated to 100℃ and kept at that temperature for 5 hours to obtain starch paste samples. The viscosity and microscopic examination of the starch paste samples were tested. Simultaneously, the volume-weighted average particle size D[4,3] (μm) and the proportion of particles with a cumulative particle size distribution <35 μm were tested in diluted starch paste samples (diluted according to Example 1). The test results are shown in Table 3 below. Microscopic examination of different amounts of starch is shown below. Figure 5 As shown.

[0067] Table 3. Results of the effects of different starch dosages on starch paste viscosity, particle size, and sedimentation volume.

[0068]

[0069] Under these conditions, with different starch concentrations, the viscosity of the gelatinized modified starch was unaffected by the average volumetric particle size and particle size distribution of the starch granules. The modified starch granules remained intact with no significant difference in size. Therefore, to obtain modified starch with higher viscosity, the average volumetric particle size after gelatinization can be controlled between 45μm and 46μm, with a particle size analysis (D < 35μm) / % ratio of 33%-34%. However, the sedimentation volume is affected by starch concentration. Under the same gelatinization conditions, the sedimentation volume of the starch paste varies; the higher the modified starch concentration, the larger the sedimentation volume. Therefore, the starch granules shown in the microscopic image can only determine the granular state after gelatinization, while the starch viscosity and sedimentation volume, which change due to starch concentration, cannot accurately reflect the degree of starch gelatinization.

[0070] The above experiments have verified that the degree of starch gelatinization is not affected by the use of modified starch of different mass concentrations, which further illustrates that the scheme of this application has a wide range of applicability.

[0071] Experimental Example 1: Accelerated Shelf Life Test

[0072] The starch paste samples obtained in Example 1 with different heat preservation times were subjected to shelf life testing at 40℃-60℃ to observe the viscosity changes and water separation of the starch paste.

[0073] Table 4. Results of viscosity and water separation changes of starch paste during shelf life at different heat preservation times.

[0074]

[0075] Table 4 shows that, through accelerated shelf-life testing of starch paste, under the condition of intact particles, the viscosity of starch paste increased within 5 hours of incubation, and no water separation occurred after 60 days of shelf-life incubation. The starch paste quality stability is good. For starch paste incubated for 6 hours, the viscosity decreased slightly and a small amount of water separation occurred after 60 days of shelf-life incubation, indicating a slight deviation in starch paste quality stability. After 6 hours of incubation, the starch viscosity continued to decrease, and the water separation gradually increased, indicating a deterioration in starch paste viscosity stability. Combining the viscosity changes, particle size and distribution, microscopic particle examination, and accelerated shelf-life results during starch gelatinization, the average volumetric particle size of modified starch was 45.53 μm, and the proportion of particles with D [<35 μm] / % was 33.5%. The starch particles were intact, resulting in higher viscosity, more complete gelatinization, and good viscosity stability. However, the sediment volume cannot accurately quantify the quality of starch gelatinization because the modified starch has the problem of broken particles due to excessive gelatinization, which leads to the inability to accurately quantify the end point of starch gelatinization quality.

[0076] Experimental Example 2: A method for controlling the degree of starch gelatinization using volume-weighted average particle size and cumulative particle size distribution. Applications in oyster sauce

[0077] Test plan:

[0078] Experimental Group 1: 15 parts oyster sauce, 9 parts white sugar, 5 parts monosodium glutamate, 6 parts edible salt, 5 parts hydroxypropyl distarch phosphate, 60 parts water, citric acid, and a certain amount of preservatives were stirred and heated until the average volume particle size of the oyster sauce was 45-46 μm and the particle size distribution D [<35 μm] / % of the oyster sauce was 33%-34%. Heating was then stopped and the mixture was cooled to 60-80℃ to obtain an oyster sauce product with a starch content of 5% (the particle size of the oyster sauce is the same as that of the starch paste; this experimental group 1 corresponds to a heat preservation time of 5 hours).

[0079] Control Group 1: 15 parts oyster sauce, 9 parts white sugar, 5 parts monosodium glutamate, 6 parts edible salt, 5 parts hydroxypropyl distarch phosphate, 60 parts water, citric acid, and a certain amount of preservatives were stirred and heated until the particle size of the oyster sauce was 46-48 μm and the particle size distribution D [<35 μm] / % was 35-36%. Heating was then stopped and the mixture was cooled to 60-80℃ to obtain an oyster sauce product with a starch content of 5% (the particle size of the oyster sauce is the same as that of the starch paste; this control group 1 corresponds to a heat preservation time of 6 hours).

[0080] Control Group 2: 15 parts oyster sauce, 9 parts white sugar, 5 parts monosodium glutamate, 6 parts edible salt, 5 parts hydroxypropyl distarch phosphate, 60 parts water, citric acid, and a certain amount of preservatives were stirred and heated until the particle size of the oyster sauce was 43-45 μm and the particle size distribution D [<35 μm] / % was 35-36%. Heating was then stopped and the mixture was cooled to 60-80℃ to obtain an oyster sauce product with a starch content of 5% (the particle size of the oyster sauce is the same as that of the starch paste; this control group 2 corresponds to a heat preservation time of 4 hours).

[0081] Control group 3: 15 parts oyster sauce, 9 parts white sugar, 5 parts monosodium glutamate, 6 parts edible salt, 5.4 parts hydroxypropyl distarch phosphate, 59.6 parts water, citric acid, and a certain amount of preservatives were stirred and heated to cook the oyster sauce until the particle size D[4,3]=41μm-43μm and D[<35μm] / %=35%-37%. After cooking, the mixture was cooled to 60-80℃ to obtain an oyster sauce product with a starch content of 5.4% (corresponding to the current gelatinization level of oyster sauce).

[0082] The detection and analysis results are shown in Table 5.

[0083] Table 5. Test results of viscosity and particle size of oyster sauce with different degrees of gelatinization.

[0084]

[0085] Accelerated shelf-life test: Oyster sauces with different degrees of gelatinization were bottled in glass bottles with a fixed weight of 700g-702g. The oyster sauces were then placed at 40℃-60℃ for shelf-life testing. The changes in viscosity of the upper layer and water separation were observed during the 15d / 30d accelerated shelf-life tests. The shelf-life test results are shown in Table 6 below:

[0086] Table 6. Results of accelerated shelf life for oyster sauces with different degrees of gelatinization.

[0087]

[0088] As shown in Tables 5 and 6, the volume-weighted average particle size D[4,3] of the gelatinized oyster sauce in Experimental Group 1 was greater than that in Control Group 3, and the cumulative particle size distribution D[<35μm] / % particle percentage was less than that in Control Group 3. Therefore, less starch was used in Experimental Group 1. Compared to Control Group 3, the starch utilization rate of Experimental Group 1 increased by approximately (5.4%-5.0%) / 5.0% = 8% (starch utilization rate is calculated based on the amount of starch used in Control Group 3). After shelf-life testing, the viscosity of the upper layer of oyster sauce remained essentially unchanged, and the amount of water separation was similar to that of the control case. After accelerated shelf-life testing, the shelf-life quality of the oyster sauce was comparable. Compared to Experimental Group 1, with the same amount of starch used, Control Group 1 had a higher viscosity of oyster sauce, but the viscosity decreased rapidly during shelf life, and water separation increased. Compared to Experimental Group 1, with the same amount of starch used, Control Group 2 had a similar shelf life of oyster sauce, but the viscosity was lower, indicating insufficient starch utilization.

[0089] By analyzing the viscosity and particle size changes of modified starch during gelatinization, the results of accelerated shelf-life testing, and the application of starch in oyster sauce products, the gelatinization quality of starch paste can be accurately quantified using volume-weighted average particle size and particle size distribution. Controlling the volume-weighted average particle size D[4,3] / μm of modified starch to 45μm-46μm, and the cumulative proportion of particles <35μm to 33%-34%, results in a starch paste with high viscosity, improved starch utilization, and good viscosity stability. This also verifies the accuracy of the evaluation method presented in this application.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A method for quantitatively evaluating the gelatinization quality of modified starch, characterized in that, Includes the following steps: S1. Prepare modified starch into starch slurry, heat and gelatinize to obtain the starch paste to be tested; S2. Dilute the starch paste obtained in step S1, and detect the first volume-weighted average particle size and the first particle size distribution accumulation of the diluted starch paste. S3. Compare the first volume-weighted average particle size and the first particle size distribution accumulation with the preset target parameter range, and evaluate the gelatinization quality of the starch paste to be tested based on the comparison results. The preset target parameter range is: volume-weighted average particle size of 45~46μm, and cumulative particle size distribution of <35μm of 33~34%.

2. The method as described in claim 1, characterized in that, In step S1, the heating temperature is 99~101℃, and the mass concentration of modified starch in the starch paste to be tested is 5.7%~6%.

3. The method as described in claim 1, characterized in that, In step S2, pure water is used as the dispersion medium to dilute the starch paste obtained in step S1 to 1%~2%. The first volume-weighted average particle size and the first particle size distribution accumulation of the diluted starch paste are detected by a laser particle size analyzer. The shading degree of the laser particle size analyzer is set to 15%~20%.

4. The method as described in claim 1, characterized in that, Step S3 includes: If the first volume-weighted average particle size is 45~46μm, and the cumulative proportion of the first particle size distribution <35μm is 33~34%, then the gelatinization quality is optimal.

5. The method according to any one of claims 1 to 3, characterized in that, The preset target parameter range is obtained through the following steps: S4. Prepare the modified starch into a starch slurry, heat and keep warm to obtain a starch paste sample; S5. Dilute the starch paste sample obtained in step S4, and detect the second volume-weighted average particle size and the second particle size distribution accumulation of the diluted starch paste sample. S6. The diluted starch paste sample obtained in step S5 is subjected to accelerated shelf life testing to detect the viscosity stability and water separation of the starch paste sample. S7. Determine the preset target parameter range based on the second volume weighted average particle size and the second particle size distribution accumulation of the diluted starch paste sample, the viscosity stability of the starch paste sample, and the water separation situation.

6. The method as described in claim 5, characterized in that, In step S4, the heating temperature is 99~101℃, and the holding time is 0~9h.

7. The method as described in claim 6, characterized in that, In step S4, the heat preservation time is 1 to 6 hours.

8. The application of the method for quantitatively evaluating the gelatinization quality of modified starch as described in any one of claims 1 to 7 in improving starch utilization.

9. The application of the method for quantitatively evaluating the gelatinization quality of modified starch as described in any one of claims 1 to 7 in the preparation of oyster sauce products.

10. The application as described in claim 9, characterized in that, The oyster sauce product comprises the following components in parts by weight: 15 parts oyster sauce, 9 parts white sugar, 5 parts monosodium glutamate, 6 parts edible salt, 5 parts hydroxypropyl distarch phosphate, and 60 parts water; the volume-weighted average particle size of the oyster sauce product is controlled to be 45~46μm, and the cumulative proportion of particles <35μm is 33~34%.

Citation Information

Patent Citations

  • Method for trace rapid detection of starch gelatinization degree

    CN107631991A

  • Wheat starch particle size analysis method

    CN108254296A

  • Piperine starch nanoparticles and preparation method thereof

    CN116407506A